2015
DOI: 10.1007/s11916-015-0500-5
|View full text |Cite
|
Sign up to set email alerts
|

Well-Established and Empirically Supported Behavioral Treatments for Migraine

Abstract: This paper provides an overview of the well-established and empirically supported behavioral interventions for the treatment of migraine. The considerable evidence base addressing behavioral interventions amassed since 1969 has conclusively established the efficacy of therapies featuring combinations of relaxation, biofeedback, and stress management training, and demonstrated they are capable of yielding benefits on par with pharmacological therapies for migraine. Behavioral interventions also are well suited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(73 citation statements)
references
References 43 publications
1
65
0
7
Order By: Relevance
“…Our findings are in accordance with the well-established use of behavioral treatment as migraine prophylaxis 36 and with recommendations of biofeedback treatment of migraine in guidelines. 37 Another metaanalysis from 2007 that investigated biofeedback as prophylactic treatment of adults with migraine concluded with a medium effect size.…”
Section: Discussionsupporting
confidence: 90%
“…Our findings are in accordance with the well-established use of behavioral treatment as migraine prophylaxis 36 and with recommendations of biofeedback treatment of migraine in guidelines. 37 Another metaanalysis from 2007 that investigated biofeedback as prophylactic treatment of adults with migraine concluded with a medium effect size.…”
Section: Discussionsupporting
confidence: 90%
“…Consortium [18] noted that, given the presence of specific factors, behavioral and other non-pharmacological treatment are preferred to pharmacological treatment for migraine headache. These factors are:patient preference for non-pharmacological treatments;poor tolerance or poor response to pharmaceuticals;negative side effects of medication;actual or planned pregnancy;history of overuse of acute care medication;significant stress;inadequate ability to cope with stress or pain;comorbid psychological disorders [19]…”
Section: Reviewmentioning
confidence: 99%
“…Penzien et al report [19] the following recommendations pertaining to behavioral interventions for migraine (as they have been outlined by the US Headache Consortium) [106]: (1) relaxation training, thermal biofeedback combined with relaxation training, electromyographic biofeedback, and cognitive behavioral therapy are treatment options for prevention of migraine (grade A evidence); and (2) behavioral therapy may be combined with preventive drug therapy to achieve added clinical improvement for migraine (grade B evidence).…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Biofeedback, one of several behavioral headache treatments, is well-established and empirically supported [9]. Systematic reviews with meta-analyses demonstrated that biofeedback is effective as a migraine prophylaxis in both the adult and pediatric populations [10,11].…”
Section: Introductionmentioning
confidence: 99%